Cancer-associated fibroblast (CAF)-derived IL32 promotes breast cancer cell invasion and metastasis via integrin β3–p38 MAPK signalling. (1st February 2019) - Wen, Siyang; Hou, Yixuan; Fu, Lixin; Xi, Lei; Yang, Dan; Zhao, Maojia; Qin, Yilu; Sun, Kexin; Teng, Yong; Liu, Manran
Abstract: Metastasis is the leading cause of breast cancer–related deaths. Cancer-associated fibroblasts (CAFs), the predominant stromal cell type in the breast tumour microenvironment, may contribute to cancer progression through interaction with tumour cells. Nonetheless, little is known about the details of the underlying mechanism. Here we found that interaction of interleukin 32 (IL32) with integrin β3 (encoded by ITGB3; a member of the integrin family) mediating the cross-talk between CAFs and breast cancer cells plays a crucial role in CAF-induced breast tumour invasiveness. IL32, an 'RGD' motif–containing cytokine, was found to be abundantly expressed in CAFs. Integrin β3 turned out to be up-regulated in breast cancer cells during epithelial–mesenchymal transition (EMT). CAF-derived IL32 specifically bound to integrin β3 through the RGD motif, thus activating intracellular downstream p38 MAPK signalling in breast cancer cells. This signalling increased the expression of EMT markers (fibronectin, N-cadherin, and vimentin) and promoted tumour cell invasion. Counteracting IL32 activity, a knockdown of IL32 or integrin β3 led to specific inactivation of p38 MAPK signalling in tumour cells. Blockage of the p38 MAPK pathway also diminished IL32-induced expression of EMT markers and breast cancer cell invasion and metastasis. Thus, our data indicate that CAF-secreted IL32 promotes breast cancer cell invasion and metastasis via integrin β3–p38 MAPK signalling. Highlights: Cancer associated fibroblasts (CAF) secreted Interleukin 32 (IL32) promotes breast cancer cells invasion and metastasis. IL32 binds to integrin β3 at the cancer cell membrane through the RGD motif. IL32-integrin β3 interaction activates P38 MAPK signalling to enhance the EMT markers expression to promote tumour invasion.